2022
DOI: 10.1002/jcla.24781
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0092887 targeting miR‐490‐5p/UBE2T promotes paclitaxel resistance in non‐small cell lung cancer

Abstract: Background Chemoresistance is a major contributing factor to cancer treatment failure. Emerging research reveals that circular RNA (circRNA) dysregulation is implicated in chemoresistance. Our current study aimed to investigate the involvement of hsa_circ_0092887 in paclitaxel (PTX) resistance in non‐small cell lung cancer (NSCLC). Methods RT‐qPCR as well as western blotting were used for the analysis of hsa_circ_0092887, miR‐490‐5p and UBE2T expression in PTX‐resistant NSCLC tumor tissues and cells. CCK‐8 ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Currently, treating tumors such as NSCLC is becoming difficult because chemotherapeutic drugs are ineffective due to resistance. It was found that the hsa_circ_0092887-mediated miR-490-5p/UBE2T signaling axis may contribute to paclitaxel-resistance intervention in NSCLC (111).…”
Section: Cancer Therapies Involving Ube2tmentioning
confidence: 99%
“…Currently, treating tumors such as NSCLC is becoming difficult because chemotherapeutic drugs are ineffective due to resistance. It was found that the hsa_circ_0092887-mediated miR-490-5p/UBE2T signaling axis may contribute to paclitaxel-resistance intervention in NSCLC (111).…”
Section: Cancer Therapies Involving Ube2tmentioning
confidence: 99%
“…Circ_0092887 inhibiting decreased cell growth and migration, while increased apoptosis in NSCLC cells treated with PTX. Circ_0092887 regulated the PTX resistance via miR-490-5p/UBE2T axis in NSCLC [ 129 ]. Matrix metalloproteinases (MMPs) are the key enzymes that break down extracellular matrix (ECM) and collagen to promote tumor angiogenesis and metastasis [ 130 ].…”
Section: Introductionmentioning
confidence: 99%